Mathematics and metaphysics: The history of the Polish philosophy of mathematics from the Romantic era - Polak, Paweł Jan (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
The Polish philosophy of mathematics in the 19th century is not a well-researched topic. For this period, only five philosophers are usually mentioned, namely Jan Śniadecki (1756–1830), Józef Maria Hoene-Wroński (1776–1853), Henryk Struve (1840–1912), Samuel Dickstein (1851–1939), and Edward Stamm (1886–1940). This limited and incomplete perspective does not allow us to develop a well-balanced picture of the Polish philosophy of mathematics and gauge its influence on 19th- and 20th-century Polish philosophy in general. To somewhat complete our picture of the history of the Polish philosophy of mathematics in those times, we here present the profiles of some lesser-known Polish Romantic philosophers of the 19th century, namely Karol Libelt, Bronisław Trentowski, and Józef Kremer. We discuss their contributions to the philosophy of mathematics and their metaphysical perspectives, and we also show how their metaphysical ideas have found some continuity in the studies of some Catholic philosophers.